Subordination of Women in Short Story of Kompas Newspaper - Sidiq Aji Pamungkas; Sarwaji Surwandi; Muhammad Rohmadi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
The equality of gender roles between men and women is a problem / polemic due to differences in gender roles. Social agreements place women to be regulated by men in life. This study discusses subordination of women in short story of Kompas newspaper on 2017. This is important to understand because understanding about subordination of women can be used as a standard of behavior to achieve harmonious and democratic community life. This type of research is descriptive qualitative with content analysis strategies. The research data was obtained from short story documents published in the Kompas newspaper in July 2017 to December 2017. The sampling technique used was purposive sampling. Data collection techniques use library research techniques. Data validity uses theory triangulation. The results showed that the subordination of women in Kompas short stories in 2017 in the form of a decision to determine the number of children was a man's decision and the decision of a girl's mate was under a man's decision as the head of the family (patriarchal culture).